Learning about healthy food through interactive game / Muhammad Faizal Samat ...[et al.] - Samat, Muhammad Faizal; Zamri, Nurul Syazwani; Ruslan, Siti Nazifa; Md Rashidi, Raznee Atisya; Mohd Kamal, Puteri Nabila (Universiti Teknologi MARA Kelantan, 2020)
Food education is very important to our life as it gives knowledge, skills and enables kids to make decisions on choosing the food that they must consume on daily life. Kids nowadays are not aware of their daily food consumption. Junk foods always be the favorites to the kids because of the flavor and some additional ingredients such as MSG that are added to the food. When the kids are addicted towards its taste, they might do not care about the quantity they consumed daily. Thus, Game of Food Block is created based on food pyramid and as an early education for kids to know about food pyramid. This interactive learning is created to entertain the children about the importance of a healthy lifestyle through food pyramid and spread the awareness about the bad of junk foods. Game of Food Block is one way to make food education become more fun and easier to learn especially for kids from the age of 3 to 12 years old because the fact says that kids learn faster than adult. This Food Block is the combination of puzzles and education, this method used because kids are highly attracted to the colorful images and moving media in games such as puzzle because it can develop problem-solving skills and strategies on how to solve the problems. This product is made for parents and teachers as a teaching tool to teach kids about the food education. Game of Food Block also can be the guideline for the kids to help them in their food consumption.